GEL EXTRACTION OF EARTHWORMS (Lumbricus rubellus) TO THE NUMBER OF FIBROBAL CELLS IN MALE WISTAR RATS (Rattus norvegiccus) GINGIVAL WOUND HEALING: PEMBERIAN GEL EKSTRAK CACING TANAH (Lumbricus rubellus) TERHADAP JUMLAH SEL FIBROBLAS PADA PENYEMBUHAN LUKA GINGIVA TIKUS WISTAR (Rattus norvegiccus) JANTAN - Ni Wayan Arni Sardi; Ni Luh Putu Sri Maryuni Adnyasari; Ni Putu Ratih Berliana Ekasari (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Gingiva is one of the oral mucosa that is most susceptible to injury, one of the factors is surgical procedures such as curettage which will be followed by a natural wound healing process. When a wound occurs, the cells that act as the building blocks of ground substance and the formation of collagen fibers in closing the wound are fibroblast cells. Many people think of earthworms (Lumbricus rubellus) only as animal feed or fish feed, but earthworms have many properties in antiperetic, antispasmodic, antidiuretic, antiasmatic, antihypertensive, antiallergic, anti-inflammatory, and have fibrinolytic activity. The purpose of this study was to determine the effect of the application of earthworm (Lumbricus rubellus) extract gel on the number of fibroblast cells in the gingival wound healing process of male Wistar (Rattus norvegicus) rats. Materials and Methods : This research method used in vivo laboratory experiments on wistar rats with three treatment groups, namely the group receiving 80% earthworm extract gel, and the control group giving placebo gel (CMC-Na 2%) which was observed on day 3. Results and Discussion: The results showed that there was a significant difference in the mean score of the number of fibroblasts on day 3 in the treatment group and the control group. The treatment group was given an 80% concentration of earthworm (Lumbricus rubellus) extract gel, which was 418.67, while the control group on day 3 was 270.33. Conclusion: It can be concluded that the gel extract of earthworm (Lumbricus rubellus) concentrate 80% is effective in increasing the number of fibroblast cells in the healing process of rat gingival wounds.